Learning Models to Improve Students' Social Skills: How is the Development Process? - Nurhadifah Amaliyah; Musdalifa; Marhani; Kartini; Burhan (Universitas Pendidikan Ganesha, 2025)
Living with other people requires communication and social skills, such as working in a team, having the determination to succeed, solving problems, communicating well, making decisions, managing oneself, and interacting with friends, so these need to be taught and trained from an early age. The development of social skills is not only related to academic aspects, but also equips students with social life skills. One way to improve social skills is through implementing the social inquiry development learning model. This learning model is designed and aims to create a learning experience that not only focuses on academic knowledge but also on developing social skills. This research approach is a Research and Development (R&D) approach using development design. The research and development procedure used is the 4-D (Four-D) model. The final product of this research is the development of an Inquiry Learning Model which has been evaluated by material experts, learning model experts, as well as limited testing. This research produces (1) The inquiry learning model can improve students' social skills. So that the inquiry learning model product is suitable for use as a learning model in the PGSD Department. (2) The Inquiry Learning Model is effectively used in social studies courses because it increases learning outcomes (Gain Score) between the experimental class and the control class.